The Effect of Unilateral Subthalamic Nucleus Deep Brain Stimulation on Contralateral Subthalamic Nucleus Local Field Potentials. Issue 4 (12th April 2020) - Hasegawa, Harutomo; Fischer, Petra; Tan, Huiling; Pogosyan, Alek; Samuel, Michael; Brown, Peter; Ashkan, Keyoumars
Abstract : Objectives: Unilateral subthalamic nucleus (STN) deep brain stimulation (DBS) for Parkinson's disease (PD) improves ipsilateral symptoms, but how this occurs is not well understood. We investigated whether unilateral STN DBS suppresses contralateral STN beta activity in the local field potential (LFP), since previous research has shown that activity in the beta band can correlate with the severity of contralateral clinical symptoms and is modulated by DBS. Materials and Methods: We recorded STN LFPs from 14 patients who underwent bilateral STN DBS for PD. Following a baseline recording, unilateral STN stimulation was delivered at therapeutic parameters while LFPs were recorded from the contralateral (unstimulated) STN. Results: Unilateral STN DBS suppressed contralateral beta power ( p = 0.039, relative suppression = −5.7% ± [SD] 16% when averaging across the highest beta peak channels; p = 0.033, relative suppression = −5.2% ± 13% when averaging across all channels). Unilateral STN DBS produced a 17% ipsilateral ( p = 0.016) and 29% contralateral ( p = 0.002) improvement in upper limb hemi‐body bradykinesia‐rigidity (UPDRS‐III, items 3.3‐3.6). The ipsilateral clinical improvement and the change in contralateral beta power were not significantly correlated. Conclusions: Unilateral STN DBS suppresses contralateral STN beta LFP. This indicates that unilateral STN DBS modulates bilateral basal ganglia networks. It remains unclear whether this mechanism accounts for the ipsilateral motor improvements.